Determination of Hodgkin and non-Hodgkin lymphoma stage with combined positron-emission and computed tomography - I. V. Boikov; G. Ye. Trufanov; V. V. Ipatov (Бюллетень сибирской медицины, 2011)
126 patients with histological diagnosis of Hodgkin and non-Hodgkin lymphoma were examined using combined positronemission and computed tomography with radiotracer 18F-deoxyglucose. For staging Ann Arbor classification (1971) with Costwolds modification (1989) was used. The combined positron-emission and computed tomography pattern of Hodgkin and non-Hodgkin lymphoma was established. Morphofunctional characteristics of lymphoma were determined in cases of lymph node, spleen, liver, kidneys, bones and lung lesion. Using combined positron-emission and computed tomography it can provide more accuracy in staging of Hodgkin and non-Hodgkin lymphoma.